Gait oxygen consumption in adolescent idiopathic scoliosis and the effect of brace use - Yurt, Yasin; Yatar, Ilker; Malkoc, Mehtap; Tuzun, Emine Handan; Mihcioglu, Serpil; Ercan, Yasemin (Elsevier Ireland Ltd, 2020)
Background: Despite studies showing that gait is affected in adolescent idiopathic scoliosis (AIS), it remains unclear whether gait oxygen consumption is altered. Research Question: The aims of the present study were to compare energy consumption during gait between subjects with AIS and healthy controls, and to examine the effect of brace use on gait energy expenditure. Methods: This prospectively designed study included 15 AIS and 15 healthy girls, whose ages ranged from 10 to 16 years old and Cobb angles from 20 and 45 degrees. At the end of the first month of brace use for the first time in individuals with AIS, oxygen consumption was measured with and without brace use on a treadmill at a gait speed of 4 km.h(-1) using a metabolic analyzer. Results: There was no statistically significant difference in gross and net gait oxygen consumption measurements between AIS and healthy individuals or between individuals with AIS with or without brace use (p > 0.05). Significance: After one month of brace treatment, AIS is not associated with an additional metabolic load with or without the brace during gait when compared to healthy subjects.
Keywords: Adolescent idiopathic scoliosis; Gait; Oxygen consumption; Bracing